Analisis Putusan Hakim dalam Tindak Pidana Pembunuhan Berencana (Putusan Nomor 1474/Pid.B/2019/PN.Dps) - Dedi Romadhan; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Interpretasi Hukum, 2021)
Sometimes in cases that have a difficulty level of proof, there is an error by the judge in proving the defendant's guilt. Such as decision number 1474 / Pid.B / 2019/ PN.Dps. According to the author, there was an error by the judge in applying the sentence to the accused. The problems are 1. What is the legal arrangement for premeditated murder? 2. What are the judges' considerations in imposing criminal sanctions against the perpetrators of the planned murder case study of Decision Number 1474 / Pid.B / 2019 / PN.Dps? The method used is normative legal research. Regulations regarding the application of the appropriate article to the accused of murder by a judge in deciding a case. In Decision Number 1474 / Pid.B/ 2019 / PN.Dps, the judge's decision to impose a sentence of premeditated murder against the defendant, according to the author, is incorrect where based on the facts in court the defendant should have been sentenced to ordinary murder. The author suggests that the judge in determining the appropriate sentence must contain basic, clear and detailed reasons. The government, especially the judiciary, must supervise and foster the judicial process in implementing penalties.